A Radiographic Study on the Associations of Age and Prevalence of Vertebral Fractures with Abdominal Aortic Calcification in Japanese Postmenopausal Women and Men. (16th November 2009) - Iwamoto, Jun; Matsumoto, Hideo; Takeda, Tsuyoshi; Sato, Yoshihiro; Uzawa, Mitsuyoshi
Abstract : The purpose of the present study was to determine the associations of age and history of non- and low-traumatic fractures with the severity of abdominal aortic calcification in Japanese postmenopausal women and men. Four hundred and one Japanese persons (24 men and 377 postmenopausal women, mean age: 73.8 years) for whom thoracic and lumbar spine radiographs had been obtained to evaluate their posture prior to patient participation in a fall-prevention exercise program were enrolled. The associations of sex, age, history of hip fracture, prevalence of vertebral fracture, and spondylosis grade (the Nathan degree) with the severity of abdominal aortic calcification (length of calcification, as evaluated according to the number of vertebral bodies) were analyzed. Nine subjects (2.2%) had a history of hip fracture, and 221 (55.1%) had at least one prevalent vertebral fracture. Two hundred and sixty-seven subjects (66.6%) had first-degree spondylosis. Age and the number of prevalent vertebral fractures, but not sex, history of hip fracture, or spondylosis grade, were significantly associated with the severity of abdominal aortic calcification. The present study confirmed that age and the number of vertebral fractures were associated with the severity of abdominal aortic calcification in Japanese postmenopausal women and men.